The dynamics of curriculum and the evolution of autonomy in learning English as a Foreign Language - Cabrales Vargas, Myriam del Carmen; Cáceres, Jaime Andrés (Íkala, Revista de Lenguaje y Cultura, 2013)
This research, carried out at the language teaching graduate program of Universidad de San Buenaventura, studies how autonomy evolves when learning English from basic to higher levels. It considers the management of learning and some components of curricular dynamics, such as the contents of subjects, classwork and independent tasks. This is a descriptive-comparative type of research of diachronic nature which, by means of analysis of quantitative and qualitative data, allowed us to characterize and compare the elements being studied. The results led to the conclusion that although the curriculum implicitly offers many elements which foster autonomy, autonomy evolves relatively slowly from one level to the other. For this reason, an organized and well supported plan to promote learners' autonomy must be implemented explicitly if students are to evolve in this area.